Stress, coping, and psychological well-being among forensic health care professionals - Elliott, Katie Ann (Legal and criminological psychology, 2013)
Purpose. Although forensic services are often regarded as highly stressful environments, there has been a surprising lack of research into the phenomena of occupational stress among forensic health care professionals (FHCP) in the United Kingdom. This study investigated stress, coping, and psychological well-being among FHCP employed within inpatient settings. Methods. One hundred and thirty-five FHCP were recruited from four Medium Secure Units in the United Kingdom. A postal research pack was used to collect background information and measures of psychological well-being, burnout, occupational stress, work satisfaction, and coping. Results. The study found that a substantial proportion of FHCP experienced elevated levels of occupational stress and psychological distress, while moderate levels of burnout were demonstrated in terms of emotional exhaustion, depersonalization, and reduced personal accomplishment. The findings confirmed that FHCP utilized a range of problem-focused (e.g., positive), emotion-focused (e.g., religious, negative, and supported), and palliative coping strategies (e.g., excessive smoking and drinking). Conclusions. The results appeared to support the commonly held assertion that forensic services are an inherently stressful and dangerous working environment, which can cause FHCP to experience marked levels of psychological distress, burnout, and occupational stress.